2017
DOI: 10.1590/1806-9282.63.07.613
|View full text |Cite
|
Sign up to set email alerts
|

Complications of central venous catheter insertion in a teaching hospital

Abstract: Introduction: Central venous catheters are fundamental to daily clinical practice. This procedure is mainly performed by residents, often without supervision or structured training. Objective: To describe the characteristics of central venous catheterization and the complication rate related to it. Method: Retrospective cohort study. Adult patients undergoing central venous catheter insertion out of the intensive care unit (ICU) of a teaching hospital were selected from March 2014 to February 2015. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
10
0
10
Order By: Relevance
“…They are primarily used when there is no peripheral access, to administer medications requiring large vessels, to provide parenteral nutrition, and to provide access for hemodialysis. [13] CVC placement is a challenging and high-risk procedure in patients, even for experienced practitioners. To date, ultrasound (US) is the method of choice for locating vessels and guiding venous punctures in adult and pediatric patients because it increases the odds of success while reducing the number of surgical attempts as well as the associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…They are primarily used when there is no peripheral access, to administer medications requiring large vessels, to provide parenteral nutrition, and to provide access for hemodialysis. [13] CVC placement is a challenging and high-risk procedure in patients, even for experienced practitioners. To date, ultrasound (US) is the method of choice for locating vessels and guiding venous punctures in adult and pediatric patients because it increases the odds of success while reducing the number of surgical attempts as well as the associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the subclavian vein is more related to pneumothorax and less related to infections, and the internal jugular vein and femoral vein are more related to arterial perforation 3 , 5 . A previous evaluation at our hospital showed that mechanical complications occurred in 6.5% of procedures and infection complications occurred in 11.1% of procedures 6 .…”
Section: Introductionmentioning
confidence: 73%
“…These analyses were conducted using SPSS 20.0 software (SPSS, Chicago, IL). Considering that in the previous study, the rate of complications of CVC insertion in the same hospital was 6% 6 , a sample size of 749 procedures was estimated for each year to identify an absolute 3% reduction in the risk of complications related to CVCs.…”
Section: Statistical Analysis Continuous Variables Are Presented As mentioning
confidence: 99%
“…Central venous catheter (CVC) placement for hemodialysis is a common procedure at large centers, although the health professionals available have not always been properly trained to conduct it. 1 Complications that have been documented include inadvertent arterial puncture with a small needle (5%), passage of the cannula through the artery (0.1 to 0.8%) and consequent hemothorax, hematoma with obstruction of airways, pseudoaneurysm, arteriovenous fistula, and encephalic vascular accident. 2 These devices are associated with around 65% of cases of deep venous thrombosis of the upper limbs, 3 and the incidence of infection is around 1.1-7.5 per 1,000 catheters inserted in cancer patients.…”
Section: Introductionmentioning
confidence: 99%